UJI ANTIBAKTERI Ag/SBA-15 DARI ABU DAUN BAMBU PETUNG TERHADAP BAKTERI Escherichia coli - Nurdahniyati Nurdahniyati; Nunung Handayani; RR Dirgarini Julia Nurlianti Subagyono; Eko Kusumawati (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2021)
Antibacterial tests of Ag/SBA-15 from petung bamboo leaf ash against Escherichia coli were carried out. Modification of SBA-15 with Ag was conducted using the wet impregnation method while the antibacterial test was carried out by well diffusion method and disc diffusion method with various concentrations of Ag/SBA-15. The Ag/SBA-15 has a surface area of ​​143 m2/g, pore diameter of 8.4 nm and pore volume of 0.35 cm3/g. The SAXS pattern of Ag /SBA-15 showed 3 typical SBA-15 peaks in the 0o -2o 2θ range with the miller index [100], [110] and [200], indicating modification with Ag did not change the hexagonal structure of SBA-15. Ag / SBA-15 material has the potential as an antibacterial agent for Escherichia coli; the inhibitory zone diameters for the well diffusion method and disc diffusion method were 7.00 ± 0.57 mm and 13.16 ± 0.16 mm, respectively. Increasing the concentration of Ag/SBA-15 samples resulted in greater inhibitory zone diameters for the bacteria.